If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(8x-3)(3x+4)(8x-5)=0
We multiply parentheses ..
(+24x^2+32x-9x-12)(8x-5)=0
| 27x2−6x=16 | | y/11=-6 | | 3r+18/9=4r-32/4 | | 3/5=y/9+1/9 | | Y=8.5x+2 | | 2-x=3x=10 | | 24x32=0 | | n/3+6=12 | | -11/5v+4/5=3 | | 3y-6+5y-10=6 | | 6.1d+23=14(d-2) | | (x+9)/(2x+1)+9=13/22 | | -11/5v4/5=3 | | 26=v/5+17 | | 1-7/2x=9/2-3/4x | | p–-5-9= -6 | | x-4√x-12=0 | | 4x-12=6(x-2) | | 8q-(5-2q)=13q+7 | | F(x)=13(182)+52 | | (5x–35)=(4x+8)=(3x+29) | | t-26=3 | | 9x+4+4x=7x+x+14 | | 17w=-68 | | 3+x(4-x)=0 | | 60/5-x=20 | | (x+9)/(2x+10)=13/22 | | -4y(24+8y)=-64 | | a/5=a-5/2 | | 4(3+3/4y)-3y=12 | | x-14+2x=13+2x-3 | | 11x–3x–3x=15 |